2022
DOI: 10.1109/access.2022.3216850
|View full text |Cite
|
Sign up to set email alerts
|

Blockchain Based Privacy Preserving Authentication and Malicious Node Detection in Internet of Underwater Things (IoUT) Networks

Abstract: Internet of Underwater Things (IoUT) Networks are used to sense different aquatic parameters like temperature, pressure, pollution, etc. They are also used to forecast the ocean's weather to collect information about natural disasters. However, they are easily compromised by attackers due to deployment in unattended environments. To overcome these issues, security is required in IoUT networks to avoid unauthorized access and ensure network credibility. This work proposes an authentication and a malicious node … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…Blockchain technology is increasingly recognized for its potential to improve communication security in IoT environments [11], [67], including the specific domain of the IoUT [9], [10]. The focus of several studies was on resolving the single point of failure problem of conventional PKI that relies on a centralized CA for issuing, maintaining, and revoking public key certificates [13], [18], [21].…”
Section: Blockchain-assisted Securitymentioning
confidence: 99%
See 2 more Smart Citations
“…Blockchain technology is increasingly recognized for its potential to improve communication security in IoT environments [11], [67], including the specific domain of the IoUT [9], [10]. The focus of several studies was on resolving the single point of failure problem of conventional PKI that relies on a centralized CA for issuing, maintaining, and revoking public key certificates [13], [18], [21].…”
Section: Blockchain-assisted Securitymentioning
confidence: 99%
“…A blockchain-based privacy-preserving authentication protocol and malicious node detection mechanism for IoUT were proposed in [9]. Similar to our approach, the authors utilize sink nodes on the surface as blockchain network for the registration and authentication of sensor nodes.…”
Section: Blockchain-assisted Securitymentioning
confidence: 99%
See 1 more Smart Citation
“…Security in IoUT networks is necessary to prevent unwanted access and to ensure network credibility, which is essential for overcoming these challenges. To prevent hostile internal nodes and untrusted external nodes from accessing the network, respectively, Abbas et al [5] suggested an authentication and harmful node detection technique. As an added layer of security and auditability, blockchain records credential hashes of registered sensor nodes.…”
Section: Attack Detection Modelsmentioning
confidence: 99%
“…The inherent limitations of their batteries render the nodes with finite storage, memory, and processing capabilities, thereby increasing their susceptibility to security breaches [4]. Energy conservation within WSNs is paramount, as the network lifetimethe duration from deployment until the depletion of the first node's energy -directly impacts the effectiveness and longevity of the network [5]. Hierarchical clustering has emerged as a prominent strategy to mitigate energy consumption and prolong the operational span of WSNs [6].…”
Section: Introductionmentioning
confidence: 99%